2006
DOI: 10.1001/archpedi.160.8.778
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Opportunistic Illnesses in Children With Human Immunodeficiency Virus in the Era of Highly Active Antiretroviral Therapy

Abstract: Opportunistic illnesses are occurring in the pediatric human immunodeficiency virus population in the HAART era, mainly in children with persistently low CD4+ T-lymphocyte percentages. Lack of a sustained response to HAART rather than age at or duration of HAART use is predictive of OI risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
27
3
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 35 publications
15
27
3
1
Order By: Relevance
“…No associations were found between survival time free of oral candidiasis and the gender or age of children living with HIV/AIDS. These results are in agreement with findings reported in a cohort of American children 33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…No associations were found between survival time free of oral candidiasis and the gender or age of children living with HIV/AIDS. These results are in agreement with findings reported in a cohort of American children 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Survival free of disease was closely linked to the degree of immunodepression, as risk increased with the exacerbation of immune system impairment. This association has been described in previous cohorts of children throughout the world 32,33,34 . However, researchers state that defenses against Candida may be compromised by HIV even before the drop in the levels of CD4+ T lymphocytes 35,36 , which may explain the appearance of thrush in individuals with HIV whose defense cell counts are within the range of normality.…”
Section: Discussionsupporting
confidence: 77%
“…Children with opportunistic infection have lower CD4 values compared to others without opportunistic infections. 10,11 In the present study, tuberculosis was found to be the commonest opportunistic infection in 25% children (including all forms of TB) with low CD4 ratio ranging from 6-32%. Similar observation was noted by Merchant et al in 84 (29.4%) patients out of 285.…”
mentioning
confidence: 50%
“…Moreover, although ART has changed the clinical course of HIV infection as mentioned above; severe drug toxicity, treatment failure, developmental delay and other unwanted outcomes are not uncommon (11)(12)(13)(14). Therefore, the objective of this study was to assess immunologic and clinical outcomes of HIV infected children on HAART in JUSH.…”
mentioning
confidence: 99%